Contextual and provenance metadata in the Oxford University Research Archive - Gray Jones, T; Burgess, L; Jefferies, N; Ranganathan, A; Rumsey, S (Springer International Publishing AG, 2015)
Context and provenance are essential for understanding the meaning and significance of an artefact. In this paper we describe how scholarly outputs deposited in a long-term data repository, the Oxford University Research Archive (ORA), are described with contextual information and provenance. In addition, the digital objects in ORA that act as proxies to the scholarly outputs are also described with contextual information and provenance. The ORA data model is presented, together with a description of the relationships in context.